2020
DOI: 10.1016/j.ajpc.2020.100037
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of in- and out-of-hospital mortality one year after acute myocardial infarction in France

Abstract: Objective To describe the spatial distribution of acute myocardial infarction (AMI) mortality in France in association with the socio-economic characteristics of the patient’s place of residence. Methods In this population-based study, we included patients hospitalized for AMI identified according to ICD-10 codes, using data from the national health insurance database from January 1, 2013 to December 31, 2014. In- and out-of-hospital deaths were identified over a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…According to Moran’s indices, there was no evidence of spatial autocorrelation during or between the three studied periods, although there were a number of zip codes with high hospitalization rates along a northeast/southwest diagonal. This finding is consistent with previous work that showed that this area had higher hospital prevalence and mortality rates than the rest of the country [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to Moran’s indices, there was no evidence of spatial autocorrelation during or between the three studied periods, although there were a number of zip codes with high hospitalization rates along a northeast/southwest diagonal. This finding is consistent with previous work that showed that this area had higher hospital prevalence and mortality rates than the rest of the country [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, no previous study has analysed small-area variation in myocardial infarction deaths and its constituents (non-fatal events and pre-hospital and post-admission deaths). Some studies have reported national data for specific countries; most of these studies relied on data from hospitalised patients (ie, excluding pre-hospital deaths), 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 and only some included pre-hospital deaths. 1 , 2 , 28 , 29 , 30 , 31 Our estimated hospital case fatality of around 11% is consistent with the national audit data report in England, 32 and within the 4–17% range in member countries of the Organisation for Economic Co-operation and Development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies conducted in New York State, and Southern West Virginia in USA, and in Denmark found associations between AMI and factors such as stress, physical inactivity, alcohol consumption, smoking, diabetes, HTN, and family history of heart disease (16)(17)(18). Research in France found higher AMI mortality rates in poorer socioeconomic areas (19), and a Libyan study revealed a significant difference in smoking rates and HTN between male and female AMI patients (20). Above studies show that the incidence of AMI varies in different regions, with factors such as HTN, smoking, and spatial accessibility to hospitals impacting the occurrence of the disease.…”
Section: Introductionmentioning
confidence: 99%